ANALISIS PENGARUH PENDAPATAN ASLI DAERAH TINGKAT INVESTASI DAN TENAGA KERJA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI KOTA LHOKSEUMAWE - Juwita Delimur Handayani; Irfan Irfan; Cut Putri Mellita Sari (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2017)
The GDP is defined as the total value added generated by all business units in an area, or the entire amount of the value of final goods and services produced by all economic units in the region. Where can describe the GDP rate of growth economic region? The high level of economic growth shown by the high value of GDP shows that the area is making progress in the economy. Kota Lhokseumawe are provinces who own a GRDP the lowest among the provinces another one where it is the dominant source of revenue for the GDP in Lhokseumawe city is influenced by three factors: the PAD, Level of Investment, and Labour, therefore, the purpose of this study is to determine how much influence PAD, Level of Investment, and Labour to the GDP in Kota Lhokseumawe. The research method using multiple regression analysis using secondary data from BPS Kota Lhokseumawe from the period 2006-2015. The results of the data analysis showed that the model of this research passes classical assumption test models with R-square of 0.948323. PAD is not positive and not significant to the GDP In the town of Lhokseumawe, Investment Rate positive and significant impact to the GDP In the town of Lhokseumawe, Labor no positive effect and are not significant to the GDP In the city of Lhokseumawe. Results from this study showed that together (Test F) a significant difference between PAD, Level Investment and Labour to the GDP.